Joseph, Judah, and Plot: an exploration of narrative continuity in Genesis 37-50 - Twiss, Paul J. (Studies in biblical literature, 2025)
"Joseph, Judah, and Plot explores the concept of narrative continuity in Genesis 37-50. By tracing the plot-structure of the story about Jacob and his sons, Twiss assesses the cohesiveness and intent of the narrative. He uses Paul Ricœur's philosophical work, Time and Narrative, as a methodological foundation to give a new, literary reading of the text. Central to the author's understanding of plot is the importance of the narrative world in which the drama unfolds, and the intended effect on the reader. When we trace the plot-structure from the narrative world to the world of the reader we see more fully its unity, and its potential to shape the minds of those who submit to its leading"--